Effect of Marination on Meat Quality and Food Safety – a Review - Raj, P Mithun Hari; Mandal, P K; Sen, A R; Kasthuri, S; Muthukumar, M (Journal of Meat Science, 2023)
Marination, infusing meat with savoury elements like spices and herbs, enhances flavour, texture, and shelf life. Marinated meat offers health benefits like antibacterial and anti-inflammatory properties, satisfying consumer preference for natural ingredients over chemical preservatives. Marination boosts sensory quality, making it vital in the meat industry for flavour, softness, and extended shelf life. Acidic marinades, like citrus and vinegar, tenderize by breaking protein bonds. Fermented dairy products improve meat quality and safety. Enzyme marinades, from fruits like kiwi, papaya, and pineapple, tenderize by breaking down meat proteins. Originating in the Mediterranean, marination improves taste, tenderness, and shelf life, reducing waste, increasing profits, and meeting consumer expectations in modern markets. Marination encompasses wet, dry, and paste methods and marinades composition affects meat microflora. Acidic marinades suppress microbial growth with weak organic acids, while LAB dominate MAP packed meat. Pseudomonas spoilage in marinated poultry is countered by LAB presence, and sodium lactate inhibits Salmonella. Weak organic acids are effective against Listeria monocytogenes, while combinations of organic acids and sodium chloride counter E. coli O157:H7. Marinades with lactic acid or sodium lactate inhibit Enterobacteriaceae and Staphylococcus aureus. Natural antioxidants, like vitamins, flavonoids, and phenolic compounds from plants, inhibit oxidation and improve sensory properties. Honey, wine, garlic, carotenoids, tocopherols, and spices such as clove, black pepper, thyme and oregano provide antioxidative and antimicrobial benefits. Charcoal cooking of meat can generate carcinogenic polycyclic aromatic hydrocarbons (PAHs). Control involves optimizing cooking methods, minimizing fat drippings, using marinades with phenolic compounds, and pairing with anti-carcinogenic foods.
Keywords: Marination; Meat Quality; Food Safety